Secondary Knee Osteoarthritis with Medial Instability and Tibial Defect due to Chronic Abscess Treated by Total Knee Arthroplasty with Metal Augmentation - Case Report - Soetjahjo, Bintang; Hancoro, Udi Herunefi; Ermawan, Rieva; Saputra, Rhyan Darma; Akbar, Hillan (Masters Program in Public Health, Sebelas Maret University, 2021)
Background:Knee osteoarthritis (OA), known as degenerative joint disease, is typically the result of wear and tear and progressive loss of articular cartilage, most common in elderly women and men. Knee OA is a leading cause of disability and increase with an aging and overweight population. Total Knee Arthroplasty (TKA) is a common surgical treatment of OA knee that highly cost-effective procedure. Stable placement of components is difficult and thus it presents technical challenges for the surgeon but various options are available for managing these defects.Case Report: A 58 years-old housewife came to our clinic due to chronic left knee pain with associated instability since two years ago and getting worse in last three months. She already had knee joint supplementation injections and physical therapy but no improvements. Based on our clinical and radiological findings, our assessment was secondary left knee osteo-arthritis with medial instability and tibial defect due to chronic abscess. Patient underwent TKA to correct this condition. A revised implant was used to close the defect in the medial part of the tibia and soft tissue reconstruction procedure was used to correct the instability.Result: On the first postoperative month, the patient underwent rehabilitation and physical therapy to strengthen her lower limb muscles. On the second month, she started to walk using walking assisted device. On the ninth months follow-up, the patient was able to walk normally without assisted device, the pain disappeared and the symptoms of knee instability were reduced.Conclusion:Bone defects are commonly encountered during TKA, which still has no standard treatment to cure. In this case, the use of metal augmentation with revision implant give satisfactory results with good clinical outcome.Keywords: Osteoarthritis, Total Knee Arthro¬plasty, knee instability, tibial defect, metal augmentationCorrespondence:Bintang Soetjahjo. Dr. Moewardi Hospital. Jl. Kolonel Sutarto 132, Jebres, Surakarta, Central Java 57126, Indonesia. Mobile: +628122987359. Email: bjortho@yahoo.comIndonesian Journal of Medicine (2021), 06(02): 168-176https://doi.org/10.26911/theijmed.2021.06.02.06